(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this paper, the effect of pollutant in environment on prey and predator species and predator harvesting is modeled using modified Leslie-Gower and nonlinear harvesting rate. Positivity and bounded of solution are proved, conditions which make the model permanent is determined, existence and locally asymptotically stable for each of possibly equilibrium point is studied, numerical solution of proposed model is done to show the effect and to confirm the analytical result.